PELATIHAN KETERAMPILAN KOMUNIKASI DAN PELAYANAN PELANGGAN BAGI WARGA DAN KARANG TARUNA DI DESA WARNASARI, PANGALENGAN KABUPATEN BANDUNG - Sudrajat, Deny; Solihin, Dewi Agustina; Purwati, Sri; Susanto, Susanto; Suryani, Suryani (POLITEKNIK LP3I JAKARTA, 2025)
Warnasari Village in Bandung Regency has quite large tourism and local economic potential, but still faces challenges in terms of the quality of human resources, especially in the aspects of communication and service. Good customer service and communication skills are important factors in supporting business development, tourism and community services in general. This community service activity aims to improve communication and customer service skills for residents and members of the Warnasari Village youth organization. The methods used are interactive training, simulations, and questions and answers and discussions. The results of the activity showed an increase in participants' understanding of the importance of effective communication and excellent service as a support for improving the quality of tourism, as well as the emergence of motivation to apply these skills in daily activities. It is hoped that this activity can contribute to strengthening local capacity and developing village potential in a sustainable manner.